Передумови створення освітньо - професійної програми технічний сервіс машин та обладнання при підготовці бакалаврів - Дідур, Володимир Аксентійович; Дидур, Владимир Аксентьевич; Didur, Volodymyr; Шокарев, Олександр Миколайович; Шокарев, Александр Николаевич; Shokarev, Oleksandr (My University, 2019)
UK: В статті розглянуто стан та мету технічного сервісу машин в Україні, доведена необхідність створення освітньо-професійної програми «технічний сервіс машин і обладнання» підготовки бакалаврів зі спеціальності 208 « Агроінженерія». EN: The article discusses the state and purpose of the technical service of machines in Ukraine, the necessity of creating an educational and professional program "technical service of machines and equipment" for the preparation of bachelors from the specialty 208 "Agroengineering" has been proved.
Precautions of creation of educational professional program technical service of machines and equipment preparing bacalavers
Keywords: технічний сервіс машин і обладнання; освітньо- професійна програма; номенклатура послуг; сфера діяльності агроінженера; technical service of machines and equipment; educationalprofessional program; nomenclature of services; sphere of activity of agroengineering